Strategi Public Relations PT Indonesia Comnets Plus dalam Meningkatkan Citra Positif Perusahaan - Susanto, Rofian Dedi; Prasetyanto, Muhammad Iqbal (LUGAS Jurnal Komunikasi, 2025)
Public Relations Strategy is a key element in the long-term success and sustainability of a Company. By focusing on the importance of public relations strategies, a Company can more easily build and enhance a positive image in the eyes of the public. This research aims to determine the public relations strategy of PT Indonesia Comnets Plus in enhancing the company's positive image, as well as identifying the challenges and efforts involved. The research method used in this study is a descriptive qualitative method with primary data collection techniques through Interviews, observations, and documentation, as well as secondary data through literature reviews using Books, Journals, and the Internet. The results of this study indicate that the element of social responsibility through the Corporate Social Responsibility (CSR) program is the most effective strategy for enhancing the positive image of PT Indonesia Comnets Plus. This is supported by other elements that help create and enhance the company's positive image as a reliable, innovative, and responsible telecommunications network service provider committed to customer satisfaction. Each of these elements has its own challenges and obstacles, requiring efforts through training and development, collaboration, consistent branding, and continuous evaluation tailored to the specific challenges of each element.